Apathy in Patients With Parkinson Disease as a Function of Side of Onset. (June 2013) - Harris, Erica; McNamara, Patrick; Durso, Raymon
Background: In previous studies among patients with Parkinson disease (PD) who were administered the Apathy Evaluation Scale (AES), between 12% and 51% evidenced clinically significant apathy. Although apathy is a risk factor for dementia, its causes and clinical correlates have not been adequately studied. In particular, side of onset of disease, though a likely predictor of apathy and dementia, has not been thoroughly investigated. Methods: A total of 30 mid-stage patients with PD and 35 community-dwelling elderly control patients (CPs) were administered the AES (self version) along with a battery of cognitive and neuropsychiatric assessments. Persons close to patients with PD and CPs completed the AES—other (informant) version about the patient or CP. Multiple linear regression analysis examined predictors of apathy severity after controlling for mood, levodopa dosage equivalents (LDEs), gender, age, and disease severity (Hoehn–Yahr [H-Y] stage). Results: Patients with right-onset disease more frequently exhibited apathy and evidenced significantly higher total AES scores than left-onset patients with PD or CPs ( P < .03). Of all the patients, 42% with right-onset PD versus 11.1% of the patients with left-onset PD exhibited clinically significant levels of apathy. There were no differences for self versus informant scores for right-onset patients with PD. The AES scores were not correlated with depression, stress, anxiety, LDEs, gender, age, and H-Y stage. There were no gender differences for any AES variables. Conclusion: Clinically significant levels of apathy are much more likely to occur in patients with right-onset disease. These patients may be at greater risk of PD-related dementia.